2007
DOI: 10.1128/cvi.00191-07
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of a Fourth Dose of Haemophilus influenzae Type b (Hib) Conjugate Vaccine and Antibody Persistence in Young Children from the United Kingdom Who Were Primed with Acellular or Whole-Cell Pertussis Component-Containing Hib Combinations in Infancy

Abstract: In response to the rising incidence of Haemophilus influenzae type b (Hib) disease in the United Kingdom, a national campaign to give a booster dose of single-antigen Hib conjugate vaccine to children aged 6 months to 4 years was undertaken in 2003. Children (n ‫؍‬ 386) eligible for Hib vaccine in the campaign were recruited. Hib antibody concentrations were measured before boost and at 1 month, 6 months, 1 year, and 2 years after boost and were analyzed according to children's ages at booster dose and whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 23 publications
(22 reference statements)
1
19
1
2
Order By: Relevance
“…This relatively poor antibody persistence was surprising, although to date, the kinetics of antibody persistence of meningococcal antibodies have not been studied. The proportions of subjects maintaining protective levels of antibodies after the administration of other conjugate vaccines such as Hib are more satisfactory following boosting, as demonstrated in this study and elsewhere (17,18). As the rate of antibody decay is similar for both PRP IgG (Ϫ1.00) and meningococcal serogroup C IgG (Ϫ0.95) following boosting, the actual magnitude of the booster response appears to determine persistence; the PRP IgG GMCs were substantially higher than the serogroup C IgG GMCs 1 month following boosting.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…This relatively poor antibody persistence was surprising, although to date, the kinetics of antibody persistence of meningococcal antibodies have not been studied. The proportions of subjects maintaining protective levels of antibodies after the administration of other conjugate vaccines such as Hib are more satisfactory following boosting, as demonstrated in this study and elsewhere (17,18). As the rate of antibody decay is similar for both PRP IgG (Ϫ1.00) and meningococcal serogroup C IgG (Ϫ0.95) following boosting, the actual magnitude of the booster response appears to determine persistence; the PRP IgG GMCs were substantially higher than the serogroup C IgG GMCs 1 month following boosting.…”
Section: Discussionsupporting
confidence: 52%
“…Comparison of the antibody kinetics with boosting (the present study) and without boosting (17) in the second year of life showed similar decay patterns (changes in the log SBA titer per log 10 unit of time, Ϫ1.60 and Ϫ1.55, respectively) (Fig. 1).…”
Section: Study Populationmentioning
confidence: 78%
See 1 more Smart Citation
“…Consequently, infants immunized with wP/PRP-T compared with aP/PRP-T have stronger responses, better persistence of anti-PRP antibodies, and less risk of vaccine failure. 51 These boosting factors may decrease in the future as widespread Hib vaccination and improved socioeconomic conditions (decreased crowding) progressively diminish upper respiratory carriage of Hib. 11,52 They would also be lower if in the future acellular pertussis vaccine came to replace whole cell pertussis in the infant combination vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Predicted vaccine effectiveness was calculated using rSBA persistence data from a clinical trial in children who received the MCC vaccine in infancy at 2, 3, and 4 months of age (from 2000 to 2003) and from whom blood samples were taken before and 4 weeks after a Hib booster dose given between 6 months and 4 years of age (30). rSBA titers were measured for these samples as previously described (6,8).…”
Section: Methodsmentioning
confidence: 99%